PERAWATAN ALAT UKUR TANAH DIGITAL - Sunar Rochmadi (Inersia : Jurnal Teknik Sipil dan Arsitektur, 2005)
ABSTRACTThis research aims to gather information of the maintenance methods fordigital surveying instruments to be ready-to-use condition. The instrumentmaintenance consists of maintenance in the laboratories including maintenanceof storing and borrowed and returned checking, and maintenance in the fieldsincluding maintenance of storing in camp, transporting, and using.This research applies descriptive-qualitative approach. The chosen researchsubjects are five surveying laboratory managers and technicians, and five seniorsurveyors, in Yogyakarta City and surroundings. The data are collected by indepthinterviews, participatory observations, and document analyses. The dataare analysed by categorization, data reduction, data display, and verificationprocesses. To achieve credibility of the research results, data triangulation isconducted, for both data sources and data collection methods.The research results show that the maintenance method in instrumentstoring, both in the laboratories and in the fields, mainly preventing humiditytriggering fungi growth and keeping instrument security. The maintenance methodin instrument